2011
DOI: 10.1111/j.1530-9134.2011.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Performance, Worker Commitment, and Loyalty

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
110
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 49 publications
9
110
1
5
Order By: Relevance
“…A series of studies have been consulted to throw light on the essence of teachers' commitment. Brown [1], for instance, concluded that teachers' commitment and loyalty are central features for better performance.…”
Section: Teachers' Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies have been consulted to throw light on the essence of teachers' commitment. Brown [1], for instance, concluded that teachers' commitment and loyalty are central features for better performance.…”
Section: Teachers' Commitmentmentioning
confidence: 99%
“…The study was guided by the following research questions: (1) What is the level of teachers' participation in decision-making among secondary school in Arusha Municipality? (2) Is there significant difference in the level of teachers' participation in decision-making between Public and Private Secondary Schools in Arusha Municipality?…”
Section: Introductionmentioning
confidence: 99%
“…He invariably posits that the efficiency of the formula (for transiting from effectiveness to greatness) would be most potent in the age of wisdom. For organizations (and by implication, for individuals in organizations) we argue that it is the combination of worker commitment and organizational citizenship behaviour that leads to the requisite greatness [8], [27, p.162]. According to Schwartz [44, p. 16-17] also, the empirical study of commitment does not quite seem to fully capture the "call" of commitment as a source of power in our lives as scientific studies often do not have the power of stories.…”
mentioning
confidence: 99%
“…Consonant with this view, Khare (2014) understands employability as a function of two basic factors: the academic qualification of an individual and the learning environment that helps the individual to build certain generic skills. This notion is supported by Brown et al (2011), who maintain that employability should exist in two domains -the absolute and the relative -with the former being the attributes of individuals and the latter being the context in which they deploy these attributes. Rae (2007) argues that a person needs more than a degree to be employable; graduates therefore need to acquire other attributes to make them employable.…”
mentioning
confidence: 98%
“…A recent study by Brown et al (2011) maintains that HE increases graduates' capabilities for gaining work. Butterwick and Benjamin (2006) argue that an employability discourse has become established in education policy, especially in developed countries.…”
mentioning
confidence: 99%